2022
DOI: 10.3390/ani12060779
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Concepts of Endometrosis, Post Breeding Endometritis, and Susceptibility of Mares

Abstract: In this paper, the evolution of our understanding about post breeding endometritis (PBE), the susceptibility of mares, and events leading to endometrosis are reviewed. When sperm arrive in the uterus, pro-inflammatory cytokines and chemokines are released. They attract neutrophils and induce modulatory cytokines which control inflammation. In susceptible mares, this physiological defense can be prolonged since the pattern of cytokine release differs from that of resistant mares being delayed and weaker for ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 107 publications
(228 reference statements)
0
23
0
3
Order By: Relevance
“…As the histopathological type of endometrosis depicted a larger modification of ECM, especially the increase in proteoglycans, fibronectin, and laminin expression [13,15], we have suggested the active remodeling of ECM in FLP. With the evolution of the concepts of equine endometrosis, it was shown that the ECM architecture and endometrial function are affected by the neutrophil extracellular traps (NETs), pro-inflammatory cytokines, pro-fibrotic pathways, growth factors and epigenetics [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the histopathological type of endometrosis depicted a larger modification of ECM, especially the increase in proteoglycans, fibronectin, and laminin expression [13,15], we have suggested the active remodeling of ECM in FLP. With the evolution of the concepts of equine endometrosis, it was shown that the ECM architecture and endometrial function are affected by the neutrophil extracellular traps (NETs), pro-inflammatory cytokines, pro-fibrotic pathways, growth factors and epigenetics [12].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the equine endometrium have focused on the molecular mechanisms involved in physiological aspects [1][2][3][4] and the pathogenesis of endometrial diseases, often associated with mares' subfertility [5][6][7][8][9]. Despite the relentless efforts and new scientific reports, the pathogenesis of nonsuppurative endometritis and endometrosis remains unknown, and routinely available treatment is still undeveloped [3,[10][11][12]. Endometrosis, also referred to as degenerative endometrial fibrosis, is the most important clinically silent endometrial disease associated with infertility in mares [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies using multivariable analysis showed an increased risk of EPL with the presence of cysts (Miyakoshi et al 2012;de Mestre et al 2019) even after maternal age and status had been accounted for in the models. It remains unclear whether the cysts themselves cause EPL and/or rather indicate underlying endometrial pathologies that could cumulate in EPL as reviewed here (Katila and Ferreira-Dias 2022). Mares can be bred on their foal heat, however, there are concerns that this practice may lead to an increased incidence of EPL.…”
Section: Reproduction Fertility and Developmentmentioning
confidence: 97%
“…In addition to infections, the immune system plays a pivotal role in this pathology in both species. By intervening in defense of the endometrium, the immune cells release pro-inflammatory cytokines and chemokines, which can themselves become a part of the inflammatory process, creating self-aggravating conditions [ 110 ]. It is currently unknown why endometritis affects some individuals rather than others.…”
Section: The Role Of the Immune System In The Pathogenesis Of The End...mentioning
confidence: 99%